Kognitivno-komunikacijska motnja - izziv v logopediji - Širca Ule, Patricija (Rehabilitacija (Ljubljana), 2015)
Damage to the right brain hemisphere may cause serious language-related problems, which also hampers communication skills of people who who this type of brain damage. A survey indicates that up to 50 % of individuals who experience this type of brain damage face communication problems. However, these problems are expressed to a different extent and in different ways, like in the case of damage to the left brain hemisphere. Damage to the right brain hemisphere may cause serious communication disorders. According to the definition of the American Speech-Language-Hearing Association (ASHA), cognitive communication disorders (CCD) encompass difficulty with any aspect of human communication that is affected by the disruption of cognition. Research has shown that approximately 50 % of people with right hemisphere brain damage have CCD. Speech-language pathologists currently have still not got appropriate diagnostic tests at their disposal that would be sensitive to CCD. Furthermore, the therapeutic approaches are poorly tested.
Keywords: Cognition Disorders; Communication Disorders; desna možganska polobla; kognitivne težave; komunikacijske težave; rehabilitacija; Rehabilitation; right brain hemisphere; vocational rehabilitation